PELABELAN TOTAL TAK REGULER PADA GRAF BARBEL - Nugroho Arif Sudibyo; Siti Komsatun (Journal of Mathematics and Mathematics Education, 2018)
Abstract:For example G (V, E) is a simple graph, a graph that do not contain of loops and parallel sides. Labeling of a graph is a mapping (function) that carries elements of a graph into positive or non-negative integers. Labeling power of irregular total point of a graph is a mapping f: VÈE ® {1, 2, 3, ..., k}which is called as labeling k total irregular point (vertex irregular total k-labeling) in G, if the weight of each different point at G is not the same, that is f(x) + ¹ f(u) + for each of the two points x and u that are different in G.Determination of exact value of irregular power of the total point is done by showing the value of lower limit and upper limit, both of them are proved to have equal value. The upper limit is decided by constructing a label, so that the largest label is obtained by minimum way. According to these two steps, a value for irregular power of the total point of a graph is obtained. In this paper, we will investigate irregular total labeling on barbell graph.Keywords:Point Irregular Total Labeling, Barbell.